The Knowledge and Practices of Mothers with 7-24 Month-Old Babies on Complementary Feeding: A Hospital-Based Research - Beyza Uçar; Özlem Öztürk Şahin (Çocuk Dergisi)
Objective: This study aims to determine the knowledge status and practices of mothers with babies aged 7-24 months about complementary feeding. Method: This is a descriptive and cross-sectional study. The study was conducted with 380 mothers who had 7-24 months old babies and were referred to the pediatric outpatient clinics of Karabük University Training and Research Hospital between 15 February and 15 May 2019. A questionnaire form consisting of four parts and containing 35 questions was used as a data collection tool in the study. Results: It was found that 75.8% of the mothers received information about breastfeeding and complementary feeding, where “nurse/midwife” (38%) ranked first among their information sources. 99.5% of the mothers started complementary feeding, where yoghurt (47.9%) ranked first among the foods they preferred for complementary feeding. When the average duration of some complementary feeding practices of mothers was examined; the mean times to start complementary feeding, to give water, to use a fork-spoon and to start solid and rough food were found as 5.48±2.09, 3.95±2.52, 6.27±1.88, and 7.02±1.84 months, respectively. A statistically significant difference was determined between the mothers’ times to start complementary feeding with respect to their education level (p=0.000), use of feeding bottles (p=0.000), use of pacifiers (p=0.001), use of baby food (p=0.000) and use of spoon food (p = 0.005). Conclusion: This study demonstrated that mothers did not have sufficient knowledge about complementary feeding, and adopted some wrong practices that might negatively affect the complementary feeding process. The study concluded that the use of feeding bottles, pacifiers, baby food and spoon formula by mothers for their babies negatively affected the transition to complementary feeding.